УЧЕБНАЯ ДЕЯТЕЛЬНОСТЬ В РАМКАХ ИНТЕГРИРОВАННОГО ПОДХОДА - Valentina Eni (Moldova State University, 2015)
În articol este investigată problema activităţiii de învăţare prin integrare în învăţământul universitar.  TRAINING ACTIVITIES WITHIN AN INTEGRATED APPROACH The article investigates issues in implementation of an integrative approach in the organization of educational activity in universities with training of specialist.